2014
DOI: 10.1111/acel.12278
|View full text |Cite
|
Sign up to set email alerts
|

Follicle‐stimulating hormone promotes age‐related endometrial atrophy through cross‐talk with transforming growth factor beta signal transduction pathway

Abstract: It is widely believed that endometrial atrophy in postmenopausal women is due to an age-related reduction in estrogen level. But the role of high circulating follicle-stimulating hormone (FSH) in postmenopausal syndrome is not clear. Here, we explored the role of high circulating FSH in physiological endometrial atrophy. We found that FSH exacerbated post-OVX endometrial atrophy in mice, and this effect was ameliorated by lowering FSH with Gonadotrophin-releasing hormone agonist (GnRHa). In vitro, FSH inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“… 44 Inhibition of TGF β signaling by blocking TGF β R2 significantly decreased FSH-mediated autophagy signaling. 45 In porcine GCs, FSH increased the level of inhibitor of NF- κ B (I κ B) protein and subsequently increased autophagy via JNK signaling. 46 In this study, we demonstrated that FSH administration enhanced autophagy in MGCs.…”
Section: Discussionmentioning
confidence: 99%
“… 44 Inhibition of TGF β signaling by blocking TGF β R2 significantly decreased FSH-mediated autophagy signaling. 45 In porcine GCs, FSH increased the level of inhibitor of NF- κ B (I κ B) protein and subsequently increased autophagy via JNK signaling. 46 In this study, we demonstrated that FSH administration enhanced autophagy in MGCs.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of FSH also impairs bone loss and further prevents LH release while the alteration does not play a dominant role in the development of osteoporosis [ 35 ]. In addition, high circulating FSH contributes to endometrial atrophy in mice [ 36 ]. Increased circulating LH may be associated with postmenopausal “hot flushes” [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since clinical studies have found improved ovarian stimulation with mixtures of acidic and less acidic hFSH isoforms (16) it will be important to determine whether mixtures of hypo-glycosylated FSH and fully-glycosylated FSH contribute to enhanced or diminished biological responses. Understanding how FSH glycoforms direct activities in multiple FSH target tissues [ovary, bone (33,34), endothelium (35), uterus and placenta (36,37)] offers a unique opportunity to develop novel approaches for diagnosis and treatments to improve fertility and reduce age associated morbidity.…”
Section: Discussionmentioning
confidence: 99%